Lung Cancer: A Review - Panda, Soumya Surath; Panda, Saroj Prasad (International Journal of Psychosocial Rehabilitation, 2019)
CT has been used recently in lung cancer mass screening. Small cancers have been identified, but these lesions do not completely recognize the growth properties of the lesions. In the three year mass CT screening program, researchers found 82 primary cancers, 61 of which were studied in present study. The volume doubling time has been determined on the basis of the exponential model using successive yearly CT images. Both cases of high resolution CT (HRCT) were also examined in the hospital. Lesions were classified into three HRCT-based types: type GS (n519), ground glass opacity (GGO); focal GGO with a solid central component; type G (n519) and solid nodule. The standard chest X-were not found in 18 (95 percent) lesions of type G, 18 (95 percent) of type GS and 7 (30 percent) of type S. For type G, type GS and type S, the maximum tumor size was 10, 11 mm and 16 mm, respectively. Adenocarcinomas were the majority of (80%) tumors; 78% were GGO ( GS and type G). The mean value of VDT for type G, GS, and type S was 813 days, 457 days and 149 days; these are somewhat far apart from each other (p.0.05). Our findings suggest that an annual CT mass screening for 3 consecutive years resulted in the recognition of several adenocarcinomas, not apparent in chestx-rays that are slowly increasing.